Revitalising Vision - An Ayurvedic Perspective in the Light of Yoga (AYUSHDHARA, 2025)
The world of technology is evolving, and this has an unanticipated negative impact on people's health, regardless of their age, gender, or financial situation. These days, people rely increasingly on technology, frequently using video conferences and zoom meetings as well as other digital platforms for business. Academically, the usage of technology has begun with virtual classrooms and online study courses. While technology keeps us connected, it also has harmful impacts on human being. Digital addiction inhibits cognitive control during emotional processing and influences social interaction. Visual work is the need of an hour and it demands continuous focusing to see the pixelated characters clearly. It is crucial to prioritise eye health in order to maintain focus on digital wellbeing. Due to prolonged focus on screen, incorrect distance between the eye and screen, unsuitable placement of computer screens and postural instability leads to various ocular and extra ocular manifestations.  The first line of action is to avoid these causal factors (Nidana Parivarjana) by minimising glare, frequent blinking, screen time reduction, and postural stability. However, yoga promotes self-regulation, which reduces the symptoms of addiction. Eye Yoga, which includes a variety of ocular exercises, Yogic Asanas, Yogic Kriya, and other preventive measures listed in classics, is seen to be a useful technique for resolving addictive behaviour.  Since the digital revolution has completely changed every industry, including education and health care, efforts have been made to use Ayurveda and Yoga to improve the vision by routinely taking care of the eyes to prevent various ocular and extra-ocular ailments.